From Pir Sain (Saint) to Lucifer: A Critical Study of Spiritual Abuse from Tehmina Durrani’s Novel ‘Blasphemy’ - Fatima, Shadab; Tarique; Khatoon, Asia; Shah, Syed Hyder Raza Shah (International Journal of Psychosocial Rehabilitation, 2020)
The present study is a comprehensive critical account of “spiritual abuse” perpetrated by a spiritual leader “Pir Sain” (the saint) and the horrible picture of Piri-Muridi (Saint-Disciple) culture practiced specifically in rural Pakistan, from Durrani’s novel Blasphemy. Spiritual Abuse is an abuse that occurs at holy places like shrines, churches, mosques, madrassahs etc that goes unquestioned as the victims, out of reverence and religious fervour do not speak up (Ward 2007). The course of events have been critically analysed against the critical ideas of various spiritual abuse theorists. The study unravels “Pir Sain” as a religious hypocrite, manipulator of the religious texts, an extreme sex addict, paedophile, and wife abuser, seducer of her own daughter and the murderer of his own son. As according to (Heil 2017), the Spiritual abuse works with thought reform or brainwashing to usurp the individual’s own way of thinking and holding control over his thought process, various elderly women like the mother of Pir Sain and his mother in law, being well aware of the Pir’s real character remained silent and also urges Heer (his wife) to be even more submissive as the submission to the Pir Sain would be rewarding in the life hereafter. The study discloses the worst modulation and usage of religion as per the wish and desire of the so-called man of God specifically in Pakistani society. The study concludes that the Pir Sain was not a messiah rather a Lucifer who exploited myriads of poor souls and devoured many lives.